From brew to table: unleashing the potential of spent grains protein - Ahuja, Vishal; Chauhan, Shikha; Yang, Yung-Hun; Bhatia, Shashi Kant; Kumar, Vinod (Elsevier, 2024)
United Nations and Upcycled Food Association have suggested the possible use of food processing residues and waste materials to improve food quality as well as overcome hunger and malnutrition. Brewer's spent grains (BSG) account 85% of brewery waste having high nutritive value. Spent grains are initially exploited for animal feed only and restricted to the local area due to high moisture content that leads to spoilage. Spent grains are rich in fibre and proteins and were explored for the preparation of cookies, bread, pasta, and noodles which showed higher nutritive value and health benefits in comparison to conventional materials. The bioactive compounds in spent grains also provide additional advantages and can be used in drug formulation for commercial products. However, it needs in-depth research and technical support that aid in contributing to the circular economy.
Keywords: Brewery spent grains; Proteins; Peptides; Bioactive compounds